Pengaruh terapi mindfulness terhadap tingkat stres pada pasien hipertensi: A systematic review - Safaruddin, Safaruddin; Christina, Tri Yahya; Sriwiyanti, Lilik; Handayani, Wiwik; Sakinah, Sri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Mindfulness therapy is a therapeutic approach that uses mindful practice to help individuals manage their thoughts, emotions, and bodily sensations in a healthy manner. Techniques such as compressions and mindful breathing have been shown to be effective in reducing stress levels, improving cognitive function, and supporting the management of chronic diseases such as hypertension. Purpose: To analyze the effect of mindfulness therapy on stress levels in patients with hypertension. Method: A systematic review and meta-analysis were designed to explore the relationship between mindfulness therapy, stress levels, and hypertension. Articles were selected based on PICO eligibility criteria and retrieved from three major databases: PubMed, Google Scholar, and ScienceDirect. Keywords used included